Internet of Things on Smart Villages - Nagabhushan Rao, M; Nikitha Sai, K; Lakshmi Deepika, C; Karthik, C (International Journal of Engineering and Technology, 2018)
The idea of internet of things plays an important role in the development of future technology. IOT is the basic vision for the future success growth in finding the new technologies. The logical basis for a course of action behind the IOT working is the result of combining or uniting all the sources of communication technologies. All the devices which are present in the system are made to function with each other , just to perform their job in a balanced manner. Due to the increase in population, it lets the city and villages to facilitate and function in a better and smarter way. Therefore, above lines put together a reason for the invention of idea of smart cities. For this to work, these cities performed two different functions. First function is all about only fetching the information from both sensors and other remote devices. Second function analyzes the information which is observed from the above function and appropriate actions are made. This paper explains the idea about smart villages, it is focused completely on villages to study them and then provide the solution for those affected areas. It also helps in the improvement of their quality of life.Â Â